HOTEL MANAGEMENT MODEL OF SELECTED STAR RATED HOTELS IN BALI - I Gusti Putu Ngurah Budiasa (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2016)
Hotel management style has been shown to be an important influence in the sustainability ofthe business. A refined model of hotel management was developed based on prior studies and literature reviews. The research reported in this article presents the results of an empir ical study whereby data were collected using in depth interviews to six successful star rated hotel managers in Bali and were analyzed using descriptive qualitative method analysis. A major finding of the study was that an effective management model is formed by a comprehensively hotel environment analysis considering both internal and external influences. The results of this investigation provide important implications for strategic hotel management concept and can aid hotel managers in improving their hotel performances and competitiveness.